OPTIMIZATION OF BELT CONVEYOR SYSTEM PERFORMANCE AT LAMPUNG PACKING PLANT THROUGH APPLICATION OF BLOCKING INDICATION SENSOR - Sabrina, Sangkot; Dani, Ahmad; Tarigan, Amani Darma (STABN RADEN WIJAYA WONOGIRI, 2024)
In various industries, the use of belt conveyors as a means of transporting materials has become very common and crucial. Belt conveyor is a production process equipment used to transport large quantities of materials. However, there are often problems with blocking cement bags on the belt conveyor which causes downtime and reduces operational efficiency. This research aims to optimize the performance of the belt conveyor through the application of a blocking indication sensor system equipped with an interlock to stop the belt conveyor motor automatically when the blocking sensor is detected. The research method consists of the design and installation of limit switch sensors, the integration of indicator light systems, and PLC-based control using ladder diagrams. Testing is carried out for one month to measure its effectiveness. The results show that the application of this sensor has succeeded in reducing downtime by 33.6%. The implementation of this system provides early warning to operators and reduces the risk of further damage, thereby significantly improving operational efficiency. This study concludes that the application of blocking indication sensors on belt conveyors is able to optimize system performance by reducing downtime and accelerating response to operational problems